Milkweed a novel - Spinelli, Jerry (Scholastic Inc., 2003)
He's a boy called Jew. Gypsy. Stopthief. Runt. Happy. Fast. Filthy son of Abraham -- He's a boy who lives in the streets of Warsaw. He's a boy who steals food for himself and the other orphans. He's a boy who believes in bread, and mothers, and angels He's a boy who wants to be a Nazi some day, with tall shiny jackboots and a gleaming Eagle hat of his own. Until the day that suddenly makes him change his mind. When the trains come to empty the Jews from the ghetto of the damned, he's a boy who realizes it's safest of all to be nobody.